2021
DOI: 10.21127/yaoyigc20200012
|View full text |Cite
|
Sign up to set email alerts
|

SnSe Solar Cells: Current Results and Perspectives

Abstract: This work presents current advances and perspectives on SnSe thin film solar cell technology. Nowadays, SnSe solar cells have not been able to achieve efficiency values higher than 7%. In this sense, it is necessary to study the potentiality of SnSe compound in solar cells that could help to understand further routes to promote this technology. It is demonstrated that efficiencies about 25% are expected under the ideal conditions of a low density of defects at SnSe bulk, the SnSe/buffer interface and the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A remarkable difference is observed between the experimental and theoretical data for SnS and SnSe solar cells without nanostructures. Taking into account conditions established by the radiative recombination, the difference between experimental and theoretical values could be a direct result of a high defect formation at bulk and interfaces, resulting in a short minority carrier lifetime, low mobility, and consequently short diffusion length of carriers, along with other factors such as non-ideal buffer layer, poor band-alignment, and losses due to reflection and series and shunt resistances as discussed in previous reports [1,29]. In this sense, further experimental studies focused on improving absorber crystalline quality, the use of an adequate buffer layer, and the reduction of the impact of resistances are needed to achieve efficiency values near the maximum values.…”
Section: Resultsmentioning
confidence: 97%
“…A remarkable difference is observed between the experimental and theoretical data for SnS and SnSe solar cells without nanostructures. Taking into account conditions established by the radiative recombination, the difference between experimental and theoretical values could be a direct result of a high defect formation at bulk and interfaces, resulting in a short minority carrier lifetime, low mobility, and consequently short diffusion length of carriers, along with other factors such as non-ideal buffer layer, poor band-alignment, and losses due to reflection and series and shunt resistances as discussed in previous reports [1,29]. In this sense, further experimental studies focused on improving absorber crystalline quality, the use of an adequate buffer layer, and the reduction of the impact of resistances are needed to achieve efficiency values near the maximum values.…”
Section: Resultsmentioning
confidence: 97%
“…21,22 These issues suggest the search for an alternative material with a less complex fabrication process, low-cost, earth-abundance, eco-friendly nature, and optoelectronic properties similar to CuInGaSe 2 and other materials. In recent times, binary element-based semiconductor materials such as SnSe thin films have gained enormous attention owing to their suitable thermoelectric [23][24][25] and optoelectronic properties, [26][27][28][29] i.e., low-cost, eco-friendliness, earthabundance, tunable bandgap (from 1.1 to 1.7 eV), high optical absorption coefficient (B10 5 cm À1 ), and chemical stability. 30 Yan et al 31 developed flexible, ultra-broadband SnSe PDs that exhibited a spectral response up to 10.6 mm enabled by the photo-bolometric effect.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 2D GeSe has attracted significant attention in the study of its application in sensors due to its smooth surface state, good stability, and anisotropic structure [26][27][28]. Recent studies have shown that 2D SnSe has good prospects in near-infrared detectors, high-performance supercapacitors, and solar cells [29][30][31][32][33][34][35]. PbSe, a member of group IV-VI monochalcogenides, was predicted to be used in diodes, infrared lasers, and sensors [36][37][38].…”
Section: Introductionmentioning
confidence: 99%